Long-term significant seasonal differences in the numbers of new-borns with an orofacial cleft in the Czech Republic - a retrospective study - Miroslav Peterka; Zbynek Likovsky; Ales Panczak; Renata Peterkova (BMC, 2018)
Abstract Background Choosing the optimal season for conception is a part of family planning since it can positively influence the pregnancy outcome. Changes in the monthly number of infants born with a birth defect can signal prenatal damage - death or malformation - related to a harmful seasonal factor. The aim of our paper was to search for possible seasonal differences in the numbers of new-borns with an orofacial cleft and thus for a period of conception that can increase the risk of orofacial cleft development. Methods Mean monthly numbers of live births in the Bohemia region of the Czech Republic during the years 1964-2000 were compared within a group of 5619 new-borns with various types of orofacial clefts and the control group derived from natality data on 3,080,891 new-borns. Results The control group exhibited regular seasonal variation in the monthly numbers of new-borns: significantly more babies born during March-May and fewer babies born during October-December. Similar natural seasonal variation was also found in the group of babies with an orofacial cleft. However, after subdividing the cleft group according to gender and cleft type, in comparison to controls, significant differences appeared in the number of new-born girls with cleft lip during January-March and in the number of boys born with cleft palate in April - May. Conclusions We found significant differences from controls in the number of new-born girls with CL and boys with CP, whose dates of birth correspond to conception from April to August and to the estimated prenatal critical period for cleft formation from May to October. The latter period includes the warm season, when various injurious physical, chemical and biological factors may act on a pregnant woman. This finding should be considered in pregnancy planning. Future studies are necessary to investigate the putative injurious factors during the warm season that can influence pregnancy outcome.